INVOLUTION IN INDONESIAN CIVILIZATION (A HISTORICAL REVIEW OF THE SOCIAL AND POLITICAL BEHAVIOR OF THE INDONESIAN SOCIETY SINCE INDEPENDENCE) - Rahman, Bustami; Sujadmi, .; Febriani, Luna (PEOPLE: International Journal of Social Sciences, 2018)
This paper begins with crucial inquiries about the process of Indonesian civilization growth: Why is the Indonesian self-identity different from those of its neighboring nations? Is there anything amiss in its process of self-making? How exactly did this nation come into being in relation with the roles of the actors involved in that process? The questions above will be responded with hypothetical answers through a historical review of the social and political behavior of the Indonesian society since its independence. Indonesia’s self-making process will be reviewed back from the period of its independence to see how its civilization grew in comparison to other nations around it. Is it true that the revolution of independence had disjointed this nation’s civilization growth process, or is there any other cause? In comparison with those of its neighboring nations, the Indonesia’s civilization growth is ratherinvolutive than evaluative, and this may not change at least for the foreseeable future. This paper aims to analyze it in a hypothetical review. The implication of this paper is the suggestion for Indonesian nation to be alert of the potential continuation of conflicts that may perpetuate the involution process, which can hamper Indonesia’s civilization growth.